THE EFFECT OF A PROBLEM-BASED LEARNING MODEL ASSISTED BY INTERACTIVE E-LKPD ON STUDENTS' MATHEMATICAL COMMUNICATION SKILLS - Riris Nur Febriani; Nurhanurawati Nurhanurawati; Mella Triana (Universitas Bhinneka PGRI, 2025)
This study aims to determine the effect of a problem-based learning model assisted by interactive E-LKPD on students' mathematical communication skills. The research design used in this study was a randomized pretest-posttest control group design. The study population was all students in grade VIII of SMP Negeri 5 Bandar Lampung in the 2024/2025 academic year, which was distributed in nine classes. The cluster random sampling technique classes VIII.5 and VIII.7 were selected as research samples. The data analyzed in this study were quantitative data obtained through a description-based test on SPLDV material. The gain score data in the experimental class was not normally distributed, and the control class was normally distributed, so the data analysis in the study used the Mann-Whitney U test with a significance level of α = 0.05. The results of the data analysis showed that the median date of the increase in the mathematical communication skills of students with the problem-based learning model assisted by interactive E-LKPD was higher than the median date of the increase in the score of mathematical communication skills of students in conventional learning. Based on the research results and discussion, it is concluded that the problem-based learning model assisted by interactive E-LKPD affects students' mathematical communication skills.